2005
DOI: 10.1093/ndt/gfi196
|View full text |Cite
|
Sign up to set email alerts
|

Increased arterial stiffness in children on haemodialysis

Abstract: We show, in this first-ever report of increased arterial stiffness in children on dialysis, that end-stage renal disease is associated with abnormalities in arterial wall elastic properties, comparable with adult levels, even in childhood. Most importantly, the absence of a discernible amelioration with dialysis implies that purely structural and not functional alterations lie behind the increased arterial stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 36 publications
7
61
1
2
Order By: Relevance
“…However, these studies in young adults can support only speculations of the potential changes in children who are on dialysis because it is possible that uremia multiplies the natural age-related vascular damage. Evidence of vascular changes in children who are on dialysis has come from observational studies that have shown increased IMT, 4 -6 stiffer vessels, 3 and calcification, 2,29,32 and linked these with PO 4 levels and Ca ϫ PO 4 ; however, patients in these studies were older than in our cohort and often had comorbidity, and the small patient numbers and widely variable duration of CKD and time on dialysis may have resulted in confounders in their analyses.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…However, these studies in young adults can support only speculations of the potential changes in children who are on dialysis because it is possible that uremia multiplies the natural age-related vascular damage. Evidence of vascular changes in children who are on dialysis has come from observational studies that have shown increased IMT, 4 -6 stiffer vessels, 3 and calcification, 2,29,32 and linked these with PO 4 levels and Ca ϫ PO 4 ; however, patients in these studies were older than in our cohort and often had comorbidity, and the small patient numbers and widely variable duration of CKD and time on dialysis may have resulted in confounders in their analyses.…”
Section: Discussionmentioning
confidence: 71%
“…Studies in adults with CKD have shown that approximately 65% have coronary calcification at the start of dialysis, 23 suggesting that prevention of secondary hyperparathyroidism is in fact key to the prevention of vascular damage and calcification. We and others have shown that endothelial dysfunction 24 and vascular damage [2][3][4][5][6] begin early in the course of CKD. The vascular damage is only partially reversible after transplantation 25 and use of lipid-lowering agents, 26 folate, 27 or arginine supplementation 28 has little effect.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Studies of children with stages 2-4 CKD and on dialysis have shown that increased intima-media thickness of the carotid artery [61,67,103] (a measure of structural changes in the vessel wall), increased pulse wave velocity [67,104,105] (a measure of stiffness or loss of compliance of the vessel) and presence of coronary and valvular calcification on CT scan [67,82,106] are present as early as the first decade of life. Secondary hyperparathyroidism, with the associated increase in calcium and phosphate levels [64], and renal bone disease [107], as well as its treatment with calcium-based phosphate binders [61,108] and vitamin D [61,67,103], have been implicated as major cardiovascular risk factors.…”
Section: Vascular Calcificationmentioning
confidence: 99%